Blue Ocean Strategy Formulation In Non Formal Education Industry Study At Bimbingan Belajar Youth Educational Centre (Yec) - Adiyatna, Hafidh Rifky (INTERNATIONAL JOURNAL OF ECONOMICS AND MANAGEMENT REVIEW, 2023)
Purpose - This study aims to identify existing attributes and offers by industry, in this case conventional learning tutors in Yogyakarta, and the other strategic independent learning groups using media books, Youtube, and others education online platform. These attributes and offering levels are represented in a value curve. After obtaining the value curve from the industry, the purpose of the next study is to formulate a new strategy for Bimbel YEC with a Blue Ocean Strategy framework. Design/methodology/approach – The study was conducted with a questionnaire instrument. Kueisoner was distributed to three groups of respondents, namely groups of respondents who gave their ratings on an ideal tutoring, a group of consumer tutoring in Yogyakarta, and consumers of Bimbel YEC. The results of the data from the first and third groups are compared, then the analysis is carried out to determine recommendations for adjustments to the offering level of each Bimbel YECs’ attribute. Adjustments are made with three main considerations. First, the difference in the expectation value of respondents with the Bimbel YECs' offering level was compared with the standard deviation of respondents' expectations. If the difference is larger than the standard deviation, an adjustment in the offering level needs to be done. The offering level is maintained if the difference between these two values is less than the standard deviation. The second consideration is made to the resources and the potential costs needed for each choice of adjustment action, especially in improving and adding attributes. The third consideration is done by comparing the offers from competitors and independent learning strategic groups whose assessments are obtained from the results of the focus group discussion. Originality - Formulation new strategy with blue ocean strategy framework for Bimbel YEC Findings and Discussion – The results of this study are recommendations for new strategies for Bimbel YEC. Bimbel YEC is recommended to focus on offering programs for grades 6, 9 and 12 for guidance on national exam preparation. In addition to the high demand of consumers, this can also increase the efficiency and effectiveness of the use of existing resources, have the opportunity to open new markets, and minimize costs incurred. The guidance process is done by a combination of offline learning and online media. This offer is not given by competitors or independent learning strategic groups. Bimbel YEC can be a learning guide with clearer positioning and can provide services with "cerdas mencerdaskan" Conclusion – Bimbel YEC is recommended to focus on offering programs for grades 6, 9 and 12 for guidance on national exam preparation. In addition to the high demand of consumers, this can also increase the efficiency and effectiveness of the use of existing resources, have the opportunity to open new markets, and minimize costs incurred.